Effects of interfacial dynamics on the damping of biocomposites - Tian, Yufeng; Kim, Wonsuk; Kiziltas, Alper; Mielewski, Deborah; Argento, Alan (Scientific reports, 2022)
A damping model is developed based on the mechanism of interfacial interaction in nanoscale particle reinforced composites. The model includes the elasticity of the materials and the effects of interfacial adhesion hysteresis. Specific results are given for the case of bio-based PA610 polyamide reinforced by nanocrystalline cellulose (CNC), based on a previous study that showed this composite possesses very high damping. The presence of hydrogen bonding at the interface between the particle and matrix and the large interfacial area due to the filler’s nano size are shown to be the main causes of the high damping enhancement. The influence of other parameters, such as interfacial distance and stiffness of the matrix materials are also discussed. The modeling work can be used as a guide in designing composites with good damping properties.